The effect of antilymphocytic antibody on the humoral immune response in different strains of mice: II. The response to sheep erythrocytes - Ghaffar, A. (1973)
The effect of an horse anti-mouse thymocyte globulin (ALG) preparation on the primary and secondary immune responses to sheep erythrocytes (RBC) was studied in 2–3-month-old male A/HeJ, C57B1, BALB/c, DBA/1, CBA and C3H mice. A wide variation in the primary and secondary responses of the individual strains was noticed but in all cases these were significantly suppressed by ALG pretreatment. The capacity of the ALG to suppress the primary immune response was not overcome by increasing the antigen dose from 3 × 10(7) to 3 × 10(9) sheep RBC.